Cross Layer Design based Hybrid Error Control for Packet Aggregation over WSN - S, Lakshmi.; Selvakumar raja.S, Dr. (International Journal of Engineering and Technology, 2018)
In general sensor networks have a wide range of application and also play a major role in developing precision and timely information. Mostly it deals with real world applications and in many cases the data sensed by the nodes should deliver within the time constriction. Meeting the deadlines is mandate for the applications and the data should be processed as soon as possible and without major data losses. The objective of this scheme is to collect data with high accuracy and low latency. Collecting and processing the data by means of aggregation will greatly reduce the congestion data rate. Cross Layer Design based Hybrid Error Control (CLDHEC) mechanism is proposed for reducing error rate occurred in sensor network which includes formation of network, data aggregation and transmission. Error control technique named Adaptive Forward Error Correction is used to defend the video transmission by recovering source information losses. FEC mechanism along with packet range control greatly increases the FEC efficiency in wireless networks. The service quality for different kind of data can be improved by lessening error rate using adaptive error control mechanism with cross layered design during packet aggregation.Â